Collective Memory, An Effective Tool for Adaptive Reuse in Modern Heritage: Challenges and Opportunities Identified in the Case of Gropius Törten Estate, Dessau - Ahmed, Sayed; Zarrin Ghalam, Sepideh; Vahabi Moghaddam, Damoun (Journal of Architectural/Planning Research and Studies (JARS), 2020)
Siedlung Gropius Törten Estate of Dessau is a social functionalist housing of Bauhaus movement. On the course of time, it is losing its originality because of technical advancement of contemporary life style. From façade color change to cutting edge installations, from social context to generation gap; it is now facing a great challenge to maintain its originality due to lack of public awareness. To understand the housing properly, literature review of previous scholars had been analyzed to know the project from every points. With enough resources prepared, an investigative social survey was conducted to compare existing literature with reality. Main approaches of collective memory were followed as method to establish effective conservation techniques in the buildings and objects those are having collective values till to date. Possible concealed implementation, installing adaptive equipment for contemporary essentials might protect its authenticity. The purpose of this research is to depict some tentative recommendations based on explicit survey results, might demonstrate the possible links for further maintainable remodeling by acknowledging the custody of Bauhaus movemment. It is also necessary to figure out the real scenario of the users and trace the public opinion. Survey results will also help to reveal the implementation scopes and various potentials in conservation techniques by focusing its integrity as modern monument in future. This study will suggest that how any neglected suburban housing could easily turn it into an income generating monumental heritage by reviving early modernism in architecture.